The Level and Development of Unemployment before Disability Retirement: A Retrospective Study of Finnish Disability Retirees and Their Controls - Laaksonen, Mikko (Int J Environ Res Public Health, 2020)
A weakening work ability may lead to a higher risk of gradual exclusion from working life, which may be manifested in increasing levels of unemployment. This study examined development of unemployment prior to disability retirement by educational level and occupational class in different diagnostic groups. The study population comprised 70% of Finnish residents aged 25–64 years who retired due to disability in 2011–2015 (n = 54,387). Growth curve models were used to analyze the level and development of pre-retirement unemployment among the retirees due to mental disorders, musculoskeletal diseases and all other somatic diseases and their gender- and age-matched controls drawn from the non-retired population. During six pre-retirement years, disability retirees had on average 39 annual excess unemployment days compared to their non-retiring controls. Excess unemployment was particularly high among those retiring due to mental disorders. On average, unemployment increased by 5.5 days per each year of approaching disability retirement, after controlling for aging and secular trends. The increase was largest among those who retired due to mental disorders. Excess unemployment was higher among the less educated and among manual workers, in particular among those retiring due to mental disorders or somatic diseases other than musculoskeletal diseases. Increased efforts to maintain and improve work ability among the unemployed is crucial in diminishing disability retirement at the population level. As the level of unemployment is elevated already several years before disability retirement, work ability problems among the unemployed should be tackled in the early stages.